Meander cutoffs nonlocally accelerate upstream and downstream migration and channel widening. Issue 24 (30th December 2016) - Schwenk, Jon; Foufoula‐Georgiou, Efi
Abstract: The hydrologic and sediment dynamics within and near cutoffs have long been studied, establishing them as effective agents of rapid local geomorphic change. However, the morphodynamic impact of individual cutoffs at the reachwide scale remains unknown, mainly due to insufficient observations of channel adjustments over large areal extents and at high temporal frequency. Here we show via annually resolved, Landsat‐derived channel masks of the dynamic meandering Ucayali River in Peru that cutoffs act as perturbations that nonlocally accelerate river migration and drive channel widening both upstream and downstream of the cutoff locations. By tracking planform changes of individual meander bends near cutoffs, we find that the downstream distance of cutoff influence scales linearly with the length of the removed reach. The discovery of nonlocal cutoff influence supports the hypothesis of "avalanche"‐type behavior in meander cutoff dynamics and presents new challenges in modeling and prediction of rivers' self‐adjusting responses to perturbations. Plain Language Summary: Meander cutoffs occur when a migrating river runs into itself. When this happens, a reach of the river is removed, or "cut off" from the main channel, and this process usually leaves behind an oxbow lake. In this work, we use satellite imagery to show, in unprecedented detail, that cutoffs along the Ucayali River in Peru drive changes to the river's shape and migration speed‐‐even far away from the cutoff location. Exactly how far away depends on the length of river removed due to the cutoff. Our results also support a model of cutoff "avalanching, " where under the right conditions, a single cutoff may spur a cluster of cutoffs nearby. This study shows how rivers adjust after cutoffs‐‐findings we might be able to apply to other types of river perturbations in the Amazon basin like deforestation, gold mining, and damming. Key Points: Annual Landsat‐derived channel masks of the Ucayali River over 31 years show planform responses to cutoffs For all 13 analyzed cutoffs the downstream extent of cutoff influence scaled with the net length of removed reach Results provide the first evidence of cutoff avalanching dynamics in meandering rivers